Class Management in Improving Mathematics Learning at SMP Negeri 1 Bilah Hilir - Hasan Hasan; Sakinah Ubudiyah Siregar (AL-ISHLAH: Jurnal Pendidikan, 2022)
Classroom management is one of the efforts to improve mathematics learning, both planning for mathematics learning. Planning is preparing mathematics learning materials that will be delivered by the teacher, what is taught is students, teachers monitor students' activities, by preparing the tools, readiness of the classroom environment, class comfort, conducive, the teacher prepares students in such a way before the mathematics learning process. Organizing is making learning tools. The online math learning uses the WhatsApp application. The mathematics learning material delivered is in the form of a file in which the file contains a photo of the material along with an explanation, a video with the material along with some exercises and assignments. Teachers are able to lead and manage classes at SMP Negeri 1 Bilah Hilir by recognizing classes that are getting bored, by changing learning methods so that students can understand mathematics learning. The evaluation carried out by the teacher saw that students were able to work on questions, assignments, exercises and exams. This is done by giving questions, quizzes, pre-tests, assignments, exercises and exams. Efforts to improve students' mathematics learning at SMP Negeri 1 Bilah Hilir are by carrying out learning activities that relate to everyday life in accordance with the learning materials. Efforts to improve it are also carried out by providing several questions, assignments, exercises and pre-tests. Efforts to improve mathematics learning teachers provide questions, assignments, exercises, with the results of these answers students are able to explain the results of answers to questions, assignments, and exercises so that there is a reciprocal effort between teachers and students